2021
DOI: 10.3390/genes12111771
|View full text |Cite
|
Sign up to set email alerts
|

A Missense Variant in the Bardet-Biedl Syndrome 2 Gene (BBS2) Leads to a Novel Syndromic Retinal Degeneration in the Shetland Sheepdog

Abstract: Canine progressive retinal atrophy (PRA) describes a group of hereditary diseases characterized by photoreceptor cell death in the retina, leading to visual impairment. Despite the identification of multiple PRA-causing variants, extensive heterogeneity of PRA is observed across and within dog breeds, with many still genetically unsolved. This study sought to elucidate the causal variant for a distinct form of PRA in the Shetland sheepdog, using a whole-genome sequencing approach. Filtering variants from a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…A MYO5A variant is reported in a single Miniature Dachshund with coat color dilution and a lethal neurological defect resembling the human Griscelli syndrome type I [16]. A new late-onset progressive retinal atrophy (PRA) in Shetland Sheepdogs that is associated with an upturned nose and coat and tooth defects was phenotypically characterized and a variant in BBS2 unraveled as the likely sole causal variant [17]. Another syndrome in Cane Corso dogs, termed the dental-skeletal-retinal anomaly, was phenotypically characterized and a causal variant in MIA3 was identified that is hypothesized to cause a defect in cellular export in the post-translational maturation of various collagens [18].…”
Section: Monogenic Inherited Diseasesmentioning
confidence: 99%
“…A MYO5A variant is reported in a single Miniature Dachshund with coat color dilution and a lethal neurological defect resembling the human Griscelli syndrome type I [16]. A new late-onset progressive retinal atrophy (PRA) in Shetland Sheepdogs that is associated with an upturned nose and coat and tooth defects was phenotypically characterized and a variant in BBS2 unraveled as the likely sole causal variant [17]. Another syndrome in Cane Corso dogs, termed the dental-skeletal-retinal anomaly, was phenotypically characterized and a causal variant in MIA3 was identified that is hypothesized to cause a defect in cellular export in the post-translational maturation of various collagens [18].…”
Section: Monogenic Inherited Diseasesmentioning
confidence: 99%
“…A close inspection of affected dogs showed that they suffered from clinical and morphological signs similar to those seen in human BBS patients such as obesity, renal abnormalities, sperm defects and anosmia ( 5 ). A missense variant in BBS2 is reported to cause syndromic PRA in Shetland sheepdogs ( 6 ). Systemic signs in the affected dogs included uncharacteristic wavy haircoat, upturned nose, dental defects, renal changes and occasional obesity ( 6 ).…”
Section: Degenerativementioning
confidence: 99%
“…A missense variant in BBS2 is reported to cause syndromic PRA in Shetland sheepdogs ( 6 ). Systemic signs in the affected dogs included uncharacteristic wavy haircoat, upturned nose, dental defects, renal changes and occasional obesity ( 6 ). A mutation in BBS4 was also described in the Hungarian puli resulting in PRA and severe reduction in sperm motility ( 7 ).…”
Section: Degenerativementioning
confidence: 99%